Hubungan Iklim Kelas dengan Kesejahteraan Psikologi Siswa - Zahrotul Mukarromah; Ellen Prima (Indo Publishing, 2026)
This study aims to analyze the relationship between classroom climate and students' psychological well-being during the learning process. A positive classroom climate plays a crucial role in creating a safe and comfortable learning environment that supports students' academic and emotional development. However, various problems persist in the school environment, such as low social support, lack of effective communication, and the emergence of academic stress, which can impact students' psychological well-being. This study employed a library research method, reviewing various scientific sources, including books, journals, and research findings relevant to the topic. Data were analyzed using a qualitative descriptive approach through the process of identifying, categorizing, and interpreting previous research findings. The results indicate that a positive classroom climate has a significant relationship with students' psychological well-being. Emotional support from teachers, open communication, harmonious social relationships, and a conducive learning environment can increase students' sense of security, motivation to learn, emotional management skills, and self-confidence. Conversely, a negative classroom climate has the potential to cause stress and anxiety, and reduce student engagement in learning. Therefore, efforts are needed from teachers and schools to create a positive classroom climate to optimally support students' psychological well-being.